The use of walkable street in the area around Masjid India, Kuala Lumpur, Malaysia - Mohamed Al Bashir, Khairi (2008)
The concept of Walkable Street is a popular concept that is widely used in urban centres of developed countries like United States of America, Britain, and in Malaysia it is still a new concept. It is obvious that the concept has contributed a great deal to the urban environment, more importantly, it has ‘returned’ the urban areas to the pedestrian to use, enjoy, shop, etc apart from the fact that walking contributes to health and reduces the negative impact of vehicular traffic. It has been proven also that, shop keepers gain substantially from increase of sale in walkable streets or areas. To the tourists, walking is the main mode of communication for them to know the life style, culture, architecture of the locals apart from doing some shopping. In relation to this, a study is conducted in a selected study site around Masjid India, Kuala Lumpur. The characteristics and parameters of “Walkable Streets” as identified in the literature review formed the basis to evaluate whether the study area meets the characteristics of walkable street. The author also by employing observation survey has identified the characteristics of urban design and quality of the built environment of the study area (building use, architecture quality, visual appropriateness, ratio of built form to urban space, traffic condition and parking facilities, and the behavior pattern of the pedestrian). Another important component is to study and evaluate the perception of the pedestrian of which a face to face questionnaire interviews were conducted in several selected locations in and around the study area. Based on the findings; issues, problems and suggestions were compiled, analyzed and finally schematic and conceptual solutions were formulated.